The Analysis of Slang Words In English Online Learning Classroom - Prayudha , Joko; Pradana, Ami (JADEs Journal of Academia in English Education, 2023)
Educational system changed to online learning because pandemic covid 19 spreads around the world. Teachers and students have to use an alternative way to carry out education through learning technology. Online learning creates a new way of communicating between teachers and students, especially when they send messages by learning platform so that in its implementation sometimes various variations appear in the use of language in learning or it is the use of slang words. The slang words are informal words or terms that have become a culture or habit in the daily conversations. This study aims to analyse the slang words used by students when learning English during online learning and also to find out the reason students use the slang words. The method used in this research was descriptive qualitative. The data was collected through the analysis of the conversation transcripts of the WhatsApp learning group and zoom comments, then an interview used to know students’ perception about slang words. The result shows that students use slang words both in Indonesian and English when chatting with friends, expressing feelings, discussing and so on. Then, there are 13 Indonesian slang words and 15 English slang words that students common use in online conversation. Next, students assume that the use of slang words can make the learning atmosphere less tense, easy to understand, to short words and make the teaching and learning process more relaxed.